Estimating the Clay Cohesion by Means of Artificial Intelligence Technique - Taha, M.R; Firoozi, A.A (Journal of Asian Scientific Research, 2012)
Sampling from the soils that reveal similar features would be difficult; even if the sample layers are from the same side. It must be also noted that the cohesion feature of the clay is one of the most important parameters of soil mechanics. In order to determine the cohesion proportion of the soil, it is necessary to perform the strength tests. If the cohesion features can be determined by means of physical parameters of soil as well as by typical fieldwork, time and cost will be saved. This article attempts at firstly performing a series of fieldwork, getting some result, and then using the existing results in order to build data bank to conduct fuzzy logical analysis. And it secondly attempts at considering the physical parameters that are effective for cohesion strength by means of artificial intelligent. Finally it attempts at comparing the results obtained from the experiments.